Long‐term human primary hepatocyte cultures in a microfluidic liver biochip show maintenance of mRNA levels and higher drug metabolism compared with Petri cultures. (20th July 2016) - Jellali, Rachid; Bricks, Thibault; Jacques, Sébastien; Fleury, Marie‐José; Paullier, Patrick; Merlier, Franck; Leclerc, Eric
Abstract: Human primary hepatocytes were cultivated in a microfluidic bioreactor and in Petri dishes for 13 days. mRNA kinetics in biochips showed an increase in the levels of CYP2B6, CYP2C19, CYP2C8, CYP3A4, CYP1A2, CYP2D6, HNF4a, SULT1A1, UGT1A1 mRNA related genes when compared with post extraction levels. In addition, comparison with Petri dishes showed higher levels of CYP2B6, CYP2C19, CYP2C8, CYP3A4, CYP1A2, CYP2D6 related genes at the end of culture. Functional assays illustrated a higher urea and albumin production over the period of culture in biochips. Bioreactor drug metabolism (midazolam and phenacetin) was not superior to the Petri dish after 2 days of culture. The CYP3A4 midazolam metabolism was maintained in biochips after 13 days of culture, whereas it was almost undetectable in Petri dishes. This led to a 5000‐fold higher value of the metabolic ratio in the biochips. CYP1A2 phenacetin metabolism was found to be higher in biochips after 5, 9 and 13 days of culture. Thus, a 100‐fold higher metabolic ratio of APAP in biochips was measured after 13 days of perfusion. These results demonstrated functional primary human hepatocyte culture in the bioreactor in a long‐term culture. Copyright © 2016 John Wiley & Sons, Ltd.